AKOMODASI KEPENTINGAN PEREMPUAN MELALUI ANGGARAN BERKEADILAN GENDER - Yusnaini .; Yulia Saftiana (Department of Accounting, Faculty of Economics, Universitas Sriwijaya, 2012)
This paper discuss how important budget gender as way to accomodate women interest. Public budgets are not merely economic tools, but summarise policies in monetery terms and express political priorities. Budgets, therefore, are not gender-neutral. They effect women and men indifferent ways, reflecting the uneven distribution of power within society as economic disparities, different living conditions and ascribed social roles. Gender budgeting seeks to make the gender impact of budgets visible and to transform them into an instrument increasing gender equality. Gender budgeting basically involves all levels of government, national, regional and local. Gender budgeting thus involves all stages of the budgetary process and implies gender-sensitive analysis, assessment and restructuring of budgets. Keyword: budget gender, public budgets, gender equality